PERAN PENTING PENGGUNAAN MEDIA VIDEO PEMBELAJARAN DALAM MATERI PEREDARAN DARAH MANUSIA KELAS 5 SEKOLAH DASAR - Dewi Putri Ramadaniyanti; Agung Setyawan (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2022)
Video media is one of the learning media that is often used by teachers in the learning and teaching process. The role of this media is very important in making it easier for students to understand material that is difficult to understand. This study aims to determine the important role of using instructional video media in the material of human blood circulation in grade 5 elementary school. The method used in this research is to use a qualitative research type. Data collection techniques using interviews and direct observation. Meanwhile, the data analysis technique produces descriptive data in the form of exposure. The results obtained from this study are the use of media that is needed and important in learning, especially in this blood circulation material. Given that science is one of the lessons that are considered difficult by students. Therefore, it is necessary for teachers to provide media or tools such as this video media in learning.